The Role of Artificial Intelligence Technologies in Customer Relationship Management: Evidence from Sudanese Telecom Companies (Sebha University Conference Proceedings, 2025)
The study aimed to examine the role of artificial intelligence (AI) technologies in customer relationship management (CRM) within Sudanese telecommunications companies. It sought to measure the level of AI usage, assess the current state of CRM, explore the relationship between AI and CRM, and test the extent of AI’s impact on CRM. The study adopted the descriptive-analytical method and utilized a questionnaire as the primary data collection tool, targeting a sample of 118 customer service employees. The findings revealed a high level of AI usage and CRM practices, along with a statistically significant correlation and impact of AI on CRM. The study recommended the continued development of AI technologies through investment in digital infrastructure within Sudanese telecom companies. It also emphasized the need for continuous updating of CRM systems, increased training programs for employees to ensure the delivery of services that meet customer needs, and the strategic adoption of AI as a tool to enhance CRM. This includes employing intelligent applications to predict customer needs and preferences and to analyze customer behavior patterns.